The role of industrial ecology in food and agriculture's adaptation to climate change. (1st April 2019) - Kendall, Alissa; Spang, Edward S.
Abstract: The food and agriculture sectors contribute significantly to climate change, but are also particularly vulnerable to its effects. Industrial ecology has robustly addressed these sectors' contributions to climate change, but not their vulnerability to climate change. Climate change vulnerability must be addressed through development of climate change adaptation and resiliency strategies. However, there is a fundamental tension between the primary objectives of industrial ecology (efficiency, cyclic flows, and pollution prevention) and what is needed for climate change adaptation and resiliency. We develop here two potential ways through which the field can overcome (or work within) this tension and combine the tools and methods of industrial ecology with the science and process of climate change adaptation. The first layers industrial ecology tools on top of climate change adaptation strategies, allowing one to, for example, compare the environmental impacts of different adaptation strategies. The other embeds climate change adaptation and resiliency within industrial ecology tools, for example, by redefining the functional unit in life cycle assessment (LCA) to include functions of resiliency. In both, industrial ecology plays a somewhat narrow role, informing climate change adaptation and resilience decision‐making by providing quantitative indicators of environmental performance. This role for industrial ecology is important given the significant contributions and potential for mitigation of greenhouse gas emissions from food and agriculture. However, it suggests that industrial ecology's role in climate adaptation will be as an evaluator of adaptation strategies, rather than an originator.